Peran pendidikan kewarganegaraan dalam mengembangkan moral melalui pembelajaran demokrasi - Ani Sulianti; Samsul Arifin; Halimatus Sakdiyah (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
Penelitian ini bertujuan untuk mengetahui: 1). Peran pendidikan kewarganegaraan dalam mengembangkan moral peserta didik, 2). Penerapan pembelajaran demokrasi dalam mengembangkan moral peserta didik. Metode penelitian yang digunakan yaitu metode kualitatif. Teknik pengumpulan data menggunakan observasi dan wawancara. Teknik pengolahan data menggunakan triangulasi. Teknik analisis data menggunakan data reduction, data display, and data conclusion drawing verification. Hasil penelitian menunjukkan bahwa 1). Pendidikan kewarganegaraan sangatlah berpengaruh dalam mengembangkan moral peserta didik dalam berinteraksi dengan lingkungan sekolah dan masyarakat 2). Demokrasi berperan penting dalam mengembangkan perilaku peserta didik dalam bersosial, bertoleransi, saling menghargai dan menghormati.Kata kunci: Perlindungan, Guru, Kekerasan, Siswa The role of civic education in developing morals through learning democracy. This study aims to in order to understand the: 1). The role of education has a hand in developing citizenship as a capital investment moral school tuition, 2). The application of democracy education has a hand in developing moral school tuition. Research methods that were used pt pgn promised to supply the qualitative method. The technique of the collection of data using observation and the objective of the interview. The technique of data processing using triangulation of. The technique of of the data analysis used data on reduction, team’s studios meeting rooms library data, a private economic analyst said the data conclusion drawing verification. The research results show that 1). Education is critical to citizenship as a capital investment has had a significant effect in developing moral school tuition of interacting with the vicinity of the school and the community 2). .Democracy play an important role in developing their activities in financing behavior school tuition in citizenchip , tolerant they begin , appreciate each other and respect .Keywords: Protection, Teacher, Violence, Students